Evaluation of a computer-model for PVDF-transducers of arbitrary configuration - SOMER, Jan; CORSEL, Jan; VANDERVOORT, Hans (Archives of Acoustics, 1988)
The electro-mechanical behaviour of PVDF can be described by the modified Mason equivalent circuit. It is possible to extract all necessary parameters and their frequency dependence from electrical input-impedance measurements and subsequent fitting-procedure with the computer-model. A chain-parameter matrix can readily be obtained for the equivalent circuit and matrix-multiplication enables the computation of any transfer function.